ANALYSIS OF DETERMINANTS OF PREECLAMPSIA IN HIGH-RISK PREGNANT WOMEN RESISTANT TO ASPIRIN PROPHYLAXIS LITERATURE REVIEW (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Preeclampsia (PE) occurs in 3–8% of pregnancies [1] and up to 20–25% in high-risk women [7], remaining a leading cause of maternal and perinatal morbidity and mortality [13]. Despite widespread use of low-dose aspirin prophylaxis, its effectiveness varies [9,10]. Analysis of recent data (Europe, Russia, Asia, Uzbekistan) shows that aspirin reduces PE risk by about 15% [12], while 6–17% of cases still develop [9,10]. Aspirin is an effective but limited preventive agent, with maximum benefit associated with early initiation and an individualized approach [1,7].